PROCESSO SUCESSÓRIO EM EMPRESAS FAMILIARES: ESTUDO DA PRODUÇÃO CIENTÍFICA INDEXADA NO REPOSITÓRIO SPELL - HAYASHI, DOUGLAS FRANCISCO (2019)
The following dissertation aims to carry out a study about the scientific production on the succession in family businesses, given the great protagonism that those businesses have in the Brazilian scenario, starting from published statistics by SEBRAE. This research presents the theories that determine the definitions of a family business, allowing a gathering of the main authors who debate over these topics, and which corroborated the idea that there is a certain stagnation on this theoretical field, although, analyzing the evolution of academic studies in the outlined period between the years of 2000 and 2018, using the extracts A-2, B-1, and B-2 from the published articles of indexed journals in SPELL as a basis, it is clear that there is a small development of the scientific production, as well as from the mapping of the articles, it was possible to pinpoint a conceptual issue about the definitions of family businesses, which demonstrates dissension amongst the authors. The question to be answered by this dissertation is: ” How are the studies on the succession in family businesses shown? ” , having as the main target the mapping of the scientific production that has been developed in the area of administration, with focus on the Identification of journals that show the studies on this subject, demonstrating the methodological approaches as well as, describing their theoretical tendencies, highlighting the most cited authors and characterizing the temporal distribution of these articles to analyze the aspects about family successions. The current study is justified by the entrepreneurial characteristics of Brazilians, who usually start their business ventures without proper planning and preparation, since 25% of family businesses do not survive the second year, and those who survive claim to face problems caused by the non-planning of the “passage of the baton”, that is, the leadership change, when, according to the studies show, only 30% of these companies survive the family succession. The methodological approach used in this dissertation is of qualitative character called State of the Art, classified as descriptive and which allowed for the elaboration of 3 categories of hindsight analysis, for instance, the corporate governance, the types of conflicts and the successors´ gender preference. Due to the used methodology, it was also possible to demonstrate inventory results which were essential for the accomplishment of the study, besides fostering the results, bringing up what was emerged in the studies of the texts. The results hereby presented show that the arising of conflicts of generations or between their heirs (horizontal conflicts), are characteristics of family businesses that go through the family succession process, as far as the matter of gender, although some texts cite that the founders are biased towards the son as their natural successor, the substantial increase of women in leadership positions demonstrates otherwise in the respective evaluated texts, breaking the paradigm of Patriarchal culture, and yet, family businesses that use corporate governance as a basic tool for guiding family successions succeed in reducing the conflicts inherent in this phase and present a decisive solution to the perpetuation and longevity of these organizations.